Nature as Limit : Prolegomena to Ecological Thinking in Heidegger - Fontini, James (Brill Fink, 2022)
Nature as Limit provides an account of Nature in terms of the collapse of the subject-object binary, presenting Heidegger's work as a series of prolegomena toward a prospective ecological thought. This begins with a critical re-evaluation of the homology Heidegger discovers between the essence of technology and the trajectory of Western metaphysics, with special attention paid to his return to Aristotle's Physics in 1939. Reimagining technics and our understanding of Nature as 'technical image', the book examines Nature as the occurrence of (de)limitation. An uncapturable immanence in the field of total phenomena, Nature is the incompletedness of any naturalism, an understanding that raises strange and compelling questions about space, time, and history. Nature as Limit confronts Heidegger's use of language on its own terms, exploring the full breadth of its intention and offering a demystification of that language, a reappraisal that offers a new lexicon for future readers.
Keywords: Heidegger, Martin, -- 1889-1976.; Heidegger, Martin, -- 1889-1976